Biochemical and technological view of broiler chicken meat with pectoral - Kato,Talita (2020)
ABSTRACT: There has been a significant advance in the poultry industry, and new technological and biological processes have accompanied the development of animals and inputs. Alongside the new possibilities for growth, there has been an emergence of new paradigms, including the rise of myopathies among which PSE, DFD, deep pectoral myopathy, oregon disease, acid breast, white stripping, wooden breast and spaghetti meat stand out. They cause considerable damage to the industry, as well as to ride hypotheses for studies in an attempt to better describe them. Researches seek to know about the behavior of proteins and specific protein groups in these anomalies. Groups of proteases are determinant to understand what may be occurring in muscle activity and; consequently, to understand the process in a more detailed way. Therefore, proteolytic systems may be acting on abnormal tissues. Proteases act differently in birds and mammals, but how altered they may be is still unknown. Besides, it is essential to relate the activities of these proteases, measures that indicate technological aspects that are relevant to meat quality standards. These quality standards must be directly associated with the consumption of raw meat in the material destined for processing, regardless of the final product. The important thing is to guarantee information that will lead the industry and consumers that will have, even with the anomaly developed, products that are nutritionally safe . This review discusses the biochemical and technological changes in poultry with pectoral anomalies, and how this affectsmeat quality.